Review of Insulin Therapy and Pen Use in Hospitalized Patients. Issue 5 (May 2013) - Davis, Estella M.; Foral, Pamela A.; Dull, Ryan B.; Smith, April N.
Objective: Hyperglycemia is common among hospitalized patients, affecting approximately 40% of patients at the time of hospital admission, despite the fact that 1 in every 8 patients has no previous diagnosis of diabetes. Hyperglycemia has been associated with poor patient outcomes, including higher rates of morbidity and mortality across a range of conditions. This review discusses options for the effective management of hyperglycemia with a focus on the use of disposable insulin pens in the hospital. Methods: Literature, including guidelines for hospital management of hyperglycemia, and information regarding methods of insulin administration were reviewed Results: Appropriate glucose control via administration of insulin within hospitals has been acknowledged as an important goal and is consistent with achieving patient safety. Insulin may be administered subcutaneously using a pen or vial and syringe or infused intravenously. Levels of patient and provider satisfaction are higher with pen administration than with vial and syringe. Insulin pens have many safety and convenience features including enhanced dose accuracy and autocover/autoshield pen needles. Conclusion: Use of insulin pens instead of vials and syringes can provide several advantages for hospitalized patients, including greater satisfaction among them and health care providers, improved safety, and reduced costs. These advantages can continue following patient discharge.